Digital twin—The dream and the reality - Kortelainen, Juha; Minav, Tatiana; Tammi, Kari (Frontiers in the Internet of Things, 2023)
Digital twins (DTs) are under active research and development in the research community, industry, and in the digital engineering solution business. The roots of the concept of DT are almost two decades old, but the fast progress in enabling technologies, especially in data analytics, artificial intelligence, and the Internet of Things, has accelerated the evolution of DT during the last five years. The growing interest, increasing development activities, and increasing business opportunities of the concept are also feeding the hype in the media. Consequently, this has led to the scattering and even misuse of the concept and its definition. In this article, we discuss different applications of DTs and what kinds of solutions there are for DTs. We analyze some most cited definitions of DT in the scientific literature and discuss the interpretation of the definitions through a hypothetical case example. Furthermore, we discuss different life cycle aspects of DTs and potential risks that may arise. To further concretize the concept of DT, we introduce ten reported case examples of implemented DTs in the scientific literature and analyze their features. Finally, we discuss the future development directions of DTs and the aspects that will affect the development trends.